BRCA1 Protein Expression in Epithelial Ovarian Cancer and Associated Clinicopathological Factors in Uganda - Tonny Okecha; Derrick B. Abila; Dorothy L. Nabbale; Fauz Katongole; James J. Yahaya; Robert Lukande; Sam Kalungi; Hawa Nalwoga (Hindawi Limited, 2024)
Conclusion: There is a high expression of altered BRCA1 expression in tissues of EOC. Although it has not shown association with age of patients, histology types, and tumor grade, further studies need to assess its influence of the survival of cancer patients with EOC.